EVALUASI SISTEM INFORMASI MANAJEMEN KEPERAWATAN BERDASARKAN PENERIMAAN PENGGUNA DI RUMAH SAKIT UMUM DAERAH (RSUD) BANYUMAS - Siti Nurhayati; Eri Wahyuningsih; Devi Octaviana; Colti Sistiarani; Jasun Jasun (Kesmas Indonesia, 2009)
Banyumas District Hospital is the pioneer in the national level of a computerbased 3N (NANDA, NIC, NOC) nursing management application. Nursing management information system in Banyumas District Hospital is a sub-system of Banyumas District Hospital’s Management Information System. Hospital’s Management Information System is a computerize system processing and integrating the whole process of health providing bussines in a coordinated networking,report and administrarion procedure to get a fast,exact,and accurate information. This research’s aim was to evaluate the nursing management information system in Banyumas District Hospital using acceptance-based of PIECES and TAM methode. The research was and explanatory research using surve in Banyumas District Hospital using acceptance-based of PIECES and TAM methode. The research was and explanatory research using survey methode and cross sectional study design. The data was analised in Spearman Rank correlation test with 0,05 significance level. The research found that the category of Banyumas District Hospital’s Nursing Management Information System is good.